Category: Maths-formula

बीजगणितीय सूत्र

बीजगणितीय सूत्र आधारभूत सूत्र (a+b)²=a²+b²+2ab (a-b)²=a²+b²-2ab a²+b²=(a+b)²-2ab a²+b²=(a-b)²+2ab (a+b)²-(a-b)²=4ab (a+b)²+(a-b)²=2(a²+b²) a²-b²=(a+b)(a-b) (a+b)³=a³+b³+3a²b+3ab² (a+b)³=a³+b³+3ab(a+b) (a-b)³=a³-b³-3a²b+3ab² (a-b)³=a³-b³-3ab(a-b) a³+b³=(a+b)(a²-ab+b²) a³+b³=(a+b)³-3ab(a+b) a³-b³=(a-b)(a²+ab+b²) a³-b³=(a-b)³+3ab(a-b) यदि a+b+c=0,तो a³+b³+c³=3abc घातांक एवम् करणी से सम्बंधित सूत्र [begin{align} & {{a}^{m}}times {{a}^{n}}={{a}^{m+n}} \ & frac{{{a}^{m}}}{{{a}^{n}}}={{a}^{m-n}} \ & {{({{a}^{m}})}^{n}}={{a}^{mn}} \ end{align}] [{(ab)^m} = {a^m} times {b^m}]